CELEBRITY ENDORSEMENT AS ONE OF NOWADYAS MAJOR WAYS TO INFLUENCE CONSUMER BUYING BEHAVIOUR - Poghosyan, Anna (European Scientific Journal, ESJ, 2015)
Celebrity endorsement as a powerful advertising instrument has nowadays became a measurable element of a marketing campaign. Companies nowadays tend to spend huge amounts on this type of advertising even despite all the involved risks with a strong believe that used celebrities will add a value to the promoted brands and will eventually influence consumers to make a purchase. The study explains how an average consumer is influenced by an advertisement which features a celebrity and also how companies manage to create beneficial associations among the promoted brands, the celebrity endorsee and a consumer by that, directing consumers in their buying decisions. The main factors which influence consumer buying behaviour are also presented in this work. The study also aims to evaluate the possible influences of celebrity endorsement on consumer buying behaviour. The initial question of the possible influences is viewed from the positive and negative aspects. First the effectiveness and positive side is presented which follows by the negative side of celebrity endorsement.